Ciclos político-econômicos e a eleição presidencial brasileira de 2014 - Bolzan, Daiane Deponti (2016)
This dissertation deals with the re-election of President Dilma in 2014 in the light of models of economic cycles incorporating federalism as an analytical element to include budgetary and voluntary transfers to municipalities. Through a Tobit model, we seek to establish whether there were changes in transfers to municipalities able to influence the vote of the government candidate. It analyzes also the “Bolsa Família” program (PBF), regional differences, the relationship between the Workers' Party (Partido dos Trabalhadores – PT) and other parties of the ruling coalition and other sociodemographic variables impacted the vote on the candidate. As a result, the current transfers of the federal government positively impact the vote on the candidate while multigovernamentals transfers has an inverse relationship with the vote. Other important results concerning the impact of PBF in the vote of the chairman and indicates that the influence caused by the program is greatly reduced. Similarly, the relationship between the mayors and governors of the main ruling party and the other coalition parties also have no major impact on the vote on the candidate. The variables that were most important in the analysis of the candidate's vote was the vote in the 2010 election, indicating the continuation of an electoral base of the PT and the HDI showed a negative relationship with the vote on the candidate.